Publication Trends In Islamic Stock Market Research: A Bibliometric Review - Noval; Rachmawati A Rifai; M. Hidayat; Fatma; Rabaniyah Istiqamah (Journal of Contemporary Economics and Business Management, 2025)
The Islamic capital market has witnessed significant growth over the past two decades, driven by a rising awareness of ethical and sustainable investments and the demand for Sharia-compliant financial solutions. Amidst the global trend towards sustainability, this market has demonstrated better resilience during economic crises, such as the COVID-19 pandemic, positioning itself as an attractive alternative for investors seeking alignment with Islamic values. This study aims to identify and analyze trends and patterns in publications related to the Islamic capital market while exploring key contributors and emerging themes in the literature. The analysis involved 747 articles authored by 1,489 contributors across 264 journals, utilizing bibliometric methods through R Biblioshiny to generate bibliometric maps. Results indicate a significant increase in publications, with an average annual growth rate of 12.74% and an average citation per document of 18.52, reflecting high relevance. Key themes include Islamic capital market performance and the COVID-19 impact. International collaboration constitutes 40.7% of publications, with leading contributors and journals highlighted.